Chronobiology of marine organisms - Naylor, Ernest (Cambridge; New York Cambridge University Press, 2010)
Table of Contents 1. Moonshine 2. Biorhythms of coastal organisms 3. Tidal and daily time-cues 4. Clocks and compasses 5. Lunar and semilunar rhythms 6. Annual biorhythms 7. Plankton vertical migration rhythms 8. Staying put in estuaries 9. Ocean drifters 10. Living clockwork.
Keywords: Marine biology; Chronobiology; Marine animals -- Life cycles